Backscattering Mueller Matrix polarimetry on whole brain specimens shows promise for minimally invasive mapping of microstructural orientation features - Bonaventura, Justina; Morara, Kellys; Carlson, Rhea; Comrie, Courtney; Daigle, Noelle; Hutchinson, Elizabeth; Sawyer, Travis W. (Frontiers in Photonics, 2022)
Understanding microscale physiology and microstructural cellular features of the brain is key to understanding mechanisms of neurodegenerative diseases and injury, as well as prominent changes undergone in development and aging. Non-invasive imaging modalities sensitive to the microscale, especially diffusion magnetic resonance imaging (dMRI), are promising for mapping of cellular microstructure of brain tissues; however, there is a need for robust validation techniques to verify and improve the biological accuracy of information derived. Recent advances in dMRI have moved toward probing of the more complex grey matter architecture, challenging current validation techniques, which are largely based on ex vivo staining and microscopy focusing on white matter. Polarized light imaging (PLI) has been shown to be successful for high resolution, direct, microstructural imaging and has been applied to dMRI validation with clear advantages over staining and microscopy techniques. Conventionally, PLI is applied to thin, sectioned samples in transmission mode, but PLI has also been extended to operate in reflectance mode to bridge the gap toward in vivo measurements of the brain. In this report we investigate the use of backscattering Mueller Matrix polarimetry to characterize the microstructural content of intact ferret brain specimens. The results show that backscattering polarimetry can probe white matter fiber coherence and fiber orientation, and show promise for probing grey matter microstructure. Ultimately, this motivates further study to fully understand how best to implement backscattering polarimetry for in vivo microstructural imaging of the brain.